Pemberdayaan Masyarakat pada Pencegahan Pernikahan Usia Dini melalui Program Jo Kawin Bocah di Kecamatan Bulu, Kabupaten Temanggung - Arneta Dyah Selina; Sungkowo Edy Mulyono (Pusat Riset dan Inovasi Nasional, 2025)
Empowerment in this context is directed at adolescents to prevent early marriage. This study aims to explain the strategies of community empowerment in preventing child marriage through the Jo Kawin Bocah program and to evaluate its level of effectiveness in Bulu Sub-district, Temanggung Regency. The targets of empowerment include adolescents, parents, community leaders, and local institutions, with a focus on enhancing knowledge, skills, and self-confidence to enable informed decision-making regarding their future, particularly in delaying marriage. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and data validation carried out using source and technique triangulation. The results show that empowerment strategies through critical education, local capacity strengthening, and advocacy are effective in fostering reflective awareness and reinforcing the community's role as agents of social change. The program has succeeded in increasing community understanding and participation, reducing the number of early marriage dispensation requests, and shaping a more critical, independent society committed to protecting children's rights.